Thermo‑mechanical properties of various densities of foamed concrete incorporating polypropylene fibres - Ahmed Jhatial, Ashfaque; Goh, Wan Inn; Sohu, Samiullah; Mohamad, Noridah (Springer, 2020)
Concrete has been extensively used in the development of urban infrastructure works. However, it has the tendency to absorb solar radiations, and these radiations are released back into the air in the form of heat energy. Dense concentration of infrastructures releases more heat, causing urban heat island (UHI) effect in which the ambient temperature of the urban areas rises slightly than the surrounding areas. Tropical countries which have a hot climate throughout the year are more affected by the UHI effect. Therefore, thermal insulating materials need to be introduced in the field of concrete construction. Foamed concrete, which has air voids in its matrix, is a potential thermal insulating material. But due to reduced density, it, however, achieves lower strength. Polypropylene (PP) fibres are used to reinforce the foamed concrete and improve its compressive and tensile strengths. In this study, three different densities, 1400, 1600 and 1800 kg/m3, were cast, and 0.8% PP fibres were added. The thermo-mechanical properties were investigated in terms of thermal conductivity, surface temperature, compressive and tensile strengths with and without the addition of PP fibres. Based on the findings, the addition of PP fibres gained more strength and reduced thermal conductivity in the lower densities of foamed concrete. In contrast, it had an opposite impact on 1800 kg/m3 density. The addition of PP fibres also indicated that it could reduce the surface temperature of higher-density foamed concrete compared to lower densities.